Menstrual symptoms and subjective well-being among postmenarchal adolescentsAJOG Global Reports at a Glance - Pietro Gambadauro, MD, MSc (Med Ed), PhD; Gergö Hadlaczky, MSc, PhD; Danuta Wasserman, MD, PhD; Vladimir Carli, MD, PhD (AJOG Global Reports, 2024)
BACKGROUND: Menstrual symptoms are predominantly studied among adults but may occur directly after menarche. Adolescent menstrual healthcare, however, faces specific obstacles and more research into menstrual symptoms as a determinant of adolescent well-being is therefore advocated. OBJECTIVE: This study aimed to investigate menstrual symptoms and their impact on everyday life and well-being among postmenarchal adolescents. STUDY DESIGN: A survey was delivered to a random sample of 1644 schoolgirls, drawn from a population-based project involving 116 lower secondary education schools (7th and 8th grade) in Stockholm, Sweden. Menstrual symptoms (ie, dysmenorrhea, heavy bleeding, irregular periods, mood disturbance, other general symptoms) were investigated through multiple choice questions and defined according to their impact on everyday life as mild (seldom affected), moderate (affected but possible to cope) and severe (affected and difficult to cope). Subjective well-being was measured with the World Health Organization Five Well-Being index. Postmenarchal respondents were eligible for analysis; those with incomplete outcome data or using hormonal contraception were excluded. The frequency and severity of symptoms across different postmenarchal years (1st, 2nd, 3rd, 4th, or 5th+ year after menarche) were studied with Chi-square and Kendall's tau statistics. Analysis of variance was used to study the association between menstrual symptoms and World Health Organization Five Well-Being index scores. A composite menstrual health index variable was obtained through principal component analysis and used to study the overall impact of menstrual symptoms on well-being in regression analyses. RESULTS: Of 1100 postmenarchal girls (mean age, 14.1±0.7 years), 93.2% reported menstrual symptoms, 81.3% had at least 1 moderate symptom and 31.3% had at least 1 severe symptom. The most frequent symptoms were dysmenorrhea (80.4%) and mood disturbance (81.1%), followed by irregular periods (67.9%), heavy bleeding (60.4%), and other general symptoms (60.4%). Throughout postmenarchal years, there was a significant increase in frequency and severity (P<.001) of dysmenorrhea (τ=0.148), heavy bleeding (τ=0.134), mood disturbance (τ=0.117), and other general symptoms (τ=0.110), but not irregular periods (τ=−0.0201; P=.434). Girls with menstrual symptoms had significantly lower World Health Organization Five Well-Being index scores than those without symptoms (mean difference, −17.3; 95% confidence interval, −22.4 to −12.3). Analysis of variance showed significant associations (P<.001) with World Health Organization Five Well-Being index scores for each of the examined menstrual symptoms. In post hoc pairwise comparisons with peers without symptoms, the greatest reductions in World Health Organization Five Well-Being index score were found among girls with severe symptoms (mean difference for: dysmenorrhea, −20.72; heavy bleeding, −15.75; irregular periods, −13.81; mood disturbance, −24.97; other general symptoms, −20.29), but significant differences were observed even for moderate or mild symptoms. The composite menstrual health index was significantly associated with World Health Organization Five Well-Being index scores in regression analysis, independently of age, age at menarche, body mass index, smoking, physical activity, own and parental country of birth, biparental care, and socioeconomic status. CONCLUSION: Despite growing awareness about the relevance of menstruation to women's health, unmet menstrual health needs are a potential threat to the well-being of adolescents. Education, screening, and clinical competence are important tools to reduce the burden of menstrual symptoms during adolescence and to prevent long-term consequences. The development of novel person-centered strategies should be a priority for clinical practice and research in adolescent menstrual health.